AB0622 Characteristics of systemic lupus erythematosus patients in malta; a population based cross-sectional cohort study. (12th June 2018) - Magro, R.; Borg, A.A.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disorder that involves multiple systems including the skin, musculoskeletal, renal, neurological, haematologic, cardiovascular and respiratory systems. Objectives: The aim of this study was to characterise the patients with systemic lupus erythematosus living in Malta, in terms of age of disease onset, BMI, co-morbidities, drug history, disease activity, damage and other factors including fatigue, sleep quality, depression, anxiety and vitamin D level. Methods: The study consisted of a cross-sectional cohort study of all known SLE patients, over the age of 18, living in Malta. 92 patients who fulfilled the SLICC classification criteria for SLE, gave informed consent and an interview was carried out. Fatigue, anxiety, depression, sleep quality and disability were assessed respectively by filling in the following questionnaires: Fatigue Severity Scale (FSS), Hospital Anxiety and Depression Scale (HADS), Pittsburgh Sleep Quality Index (PSQI) and modified Health Assessment Questionnaire (mHAQ). Results: 92.4% of SLE patients studied were female. Table 1 summarises the characteristics of the SLE patients. 23.9% of SLE patients were in remission (SLEDAI-2K 0), while 52.2% had a low disease activity (SLEDAI-2K 1–5) at the time of the interview. 20.7% and 3.3% had a moderate (SLEDAI-2K 6–10) and high (SLEDAI-2K 11–19) disease activity respectively. A significant positive correlation was noted between function measured by mHAQ and SLEDAI (R=0.417, p=0.000). 56.5% were noted to have an abnormally high level of fatigue (FSS >3.7). 6.5% were noted to have depression (HADS D>10) and 35.9% had anxiety (HADS A>10). 55.4% were noted to have poor sleep quality (PSQI >5) and 26.1% had an abnormal level of function (mHAQ >0.3). 15.2% were found to have vitamin D deficiency and 27.2% were vitamin D insufficient. Conclusions: This is the first population based study on SLE to be carried out in Malta. The prevalence of SLE in Malta is estimated to be 25.5 patients per 1 00 000 and the estimated incidence is 1.05 patients per 1 00 000 per year. A high frequency of obesity and vitamin D deficiency and insufficiency were noted in SLE patients. Other unmet needs include an uncontrolled disease activity, fatigue, poor sleep quality and anxiety. Disclosure of Interest: None declared